Expression and Prognostic Role of Glia Maturation Factor-γ in Gliomas - Liu, Junhui; Zhu, Xiaonan; Gao, Lun; Geng, Rongxin; Tao, Xiang; Xu, Haitao; Chen, Zhibiao (Frontiers in Molecular Neuroscience, 2022)
Background Glia maturation factor-γ (GMFG) regulates actin cytoskeletal organization and promotes the invasion of cancer cells. However, its expression pattern and molecular function in gliomas have not been clearly defined. Methods In this study, public datasets comprising 2518 gliomas samples were used to explore GMFG expression and its correlation with malignancy in gliomas. Immunohistochemistry (IHC) staining was performed to determine the expression of GMFG in gliomas using an in-house cohort that contained 120 gliomas samples. Gene ontology enrichment analysis was conducted using DAVID tool. The correlation between GMFG expression and immune cells infiltration was evaluated using TIMER, TISCH database, and IHC staining assays. Kaplan-Meier analysis was performed to determine the prognostic role of GMFG and its association with Temozolomide (TMZ) response in gliomas. Results GMFG expression was higher in gliomas compared with non-tumor brain tissues both in public datasets and in-house cohort. High expression of GMFG significantly associated with WHO grade IV, IDH 1/2 wildtype, and mesenchymal subtypes. Bioinformatic prediction and IHC analysis revealed that GMFG expression obviously correlated with the macrophage marker CD163 in gliomas. Moreover, both lower grade glioma (LGG) and glioblastoma multiforme (GBM) patients with high GMFG expression had shorter overall survival than those with low GMFG expression. These results indicate that GMFG may be a therapeutic target for the treatment of such patients. Patients with low GMFG expression who received chemotherapy had a longer survival time than those with high GMFG expression. For patients who received ion radiotherapy (IR) only, the GMFG expression level had no effect on the overall survival neither in CGGA and TCGA datasets Conclusion The GMFG is a novel prognostic biomarker both LGG and GBM patients. Increased GMFG expression is associated with tumor associated macrophages(TAMs) infiltration and with a bad response to TMZ treatment.